Long-Term Follow-Up of Combined Photorefractive Keratectomy and Corneal Crosslinking in Keratoconus Suspects - Kymionis G (Dove Medical Press, 2021)
George Kymionis,1 George Kontadakis,1,2 Michael Grentzelos,1 Myrsini Petrelli1 1Department of Ophthalmology, University of Lausanne, Jules-Gonin Eye Hospital, Fondation Asile des Aveugles, Lausanne, Switzerland; 2Laboratory of Vision and Optics, University of Crete, Heraklion, GreeceCorrespondence: George KontadakisLaboratory of Vision and Optics, University of Crete, Heraklion, GreeceEmail kontadas@yahoo.comPurpose: To present the long-term outcomes of photorefractive keratectomy (PRK) combined with accelerated corneal cross-linking (CXL) for refractive error correction in a series of keratoconus suspects.Setting: University practice.Design: Retrospective case series.Methods: A series of patients with topographic findings suspicious for keratoconus underwent simultaneous PRK and prophylactic accelerated CXL (5 minutes with intensity of 18 mW/cm2) for the correction of their refractive error. The results were recorded for more than 4 years postoperatively.Results: Ten eyes of 5 patients were included. Mean follow-up was 58.2 months (range from 54 to 62 months). Mean age at presentation was 25 years (range from 22 to 32 years). Mean spherical equivalent (SE) refraction was − 2.76 (standard deviation [SD] 0.97D, range from − 1.25 to − 4.00 diopters [D]), while mean central corneal thickness was 511μm (SD 13μm, range from 485 to 536 μm). At last, follow-up 9 out of 10 eyes had SE refraction within ± 0.50D and all eyes had SE within ± 1.00D. None of the eyes lost any line of corrected distance visual acuity (CDVA), whereas 1 eye gained one line of CDVA. All eyes demonstrated stability of their results during the follow-up period.Conclusion: Simultaneous PRK followed by prophylactic accelerated CXL (PRK plus) appeared to be a safe and effective option for the correction of the refractive error in this series of keratoconus suspect patients, without compromising corneal stability for up to 5 years postoperatively.Keywords: corneal crosslinking, photorefractive keratoplasty, forme fruste keratoconus, corneal topography, irregular astigmatism